2002
DOI: 10.1080/00207450290158269
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: NO EFFECT OF LONG-TERM VALPROATE THERAPY ON THYROID AND PARATHYROID FUNCTIONS IN CHILDREN

Abstract: In this study, we studied serum calcium, phosphorus, alkaline phosphatase, thyroid hormones (total thyroxine, free thyroxine, thyroid-stimulating hormone), parathyroid hormone, and osteocalcine levels in children with epilepsy who had been receiving long-term valproate (VPA) therapy in order to determine whether there was any effect of VPA therapy on these hormones. The study included 31 patients with epilepsy receiving VPA and 22 healthy age-matched controls. The age ranged from 15 months to 16 years and 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…According to some authors, serum FT3 during VPA treatment can remain unchanged (Caksen et al ., ; Verrotti et al ., ; Aggarwal et al ., ; Aygun et al ., ) or decrease (Eiris‐Punal et al ., ). Our study demonstrated significantly higher serum FT3 in the VPA group, compared to healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to some authors, serum FT3 during VPA treatment can remain unchanged (Caksen et al ., ; Verrotti et al ., ; Aggarwal et al ., ; Aygun et al ., ) or decrease (Eiris‐Punal et al ., ). Our study demonstrated significantly higher serum FT3 in the VPA group, compared to healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…Serum FT4 concentrations in our study were within the normal range, and this is in agreement with some previously published data (Caksen et al ., ; Vainionpaa et al ., ; Verrotti et al ., ). However, other authors reported serum FT4 to be significantly lower in patients receiving VPA treatment despite their clinically euthyroid status (Specchio et al ., ; Castro‐Gago et al ., ; Hirfanoglu et al ., ; Aygun et al ., ; Doneray et al ., ; Turan et al ., ; Yilmaz et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one study has found that children administered VPA for epilepsy showed evidence of hypothyroidism [179], while another study suggested that VPA was associated with increases in thyroid stimulating hormone [116]. However, these findings have not been replicated [180] and do not provide substantial evidence that VPA clinically affects thyroid function. Nonetheless, thyroid function remains an important point of clinical care for women with bipolar disorder, as it has a higher rate of dysfunction in this population and is associated with lithium use.…”
Section: Estrogen Progesterone and Thyroid Hormonesmentioning
confidence: 97%
“…A recent systematic review of the untoward effects of valproate showed that drug-induced parkinsonism is a relatively common side effect in elderly women 6 . It's known that valproate can safely be used in patients with thyroid and parathyroid dysfunction, once it does not interfere on these hormone levels 7 . The mechanism of how valproate can induce trismus is unclear.…”
Section: Dear Editormentioning
confidence: 99%